“Great Flood-Gates of the Wonder World”: Baptisms of Water and Fire in Melville and Hawthorne - Ariel Clark Silver (European Journal of American Studies)
In “Hawthorne and His Mosses,” Melville writes that “it is hard to be finite upon an infinite subject, and all subjects are infinite” (1170). Both Melville and Hawthorne take on subjects of infinitude and read them through elements essential to both spiritual and physical realms: water and fire. When John the Baptist speaks of baptisms of water and fire in the Gospel of Matthew (3:11), he prefigures the mortal and metaphysical obsessions in which Melville and Hawthorne find themselves immersed. The better part of Melville’s oeuvre—Typee, Omoo, Redburn, White-Jacket, Moby-Dick, and Billy Budd, Sailor—is baptized in water. Like Ishmael in Moby-Dick, Melville wishes to “sail forbidden seas, and land on barbarous coasts” (Moby-Dick 8). As Mary Bryden asserts, “the sea is the fluid medium, the agency, the culture” (107) through which Melville explores the philosophical depths and searches for elusive truth. He is astonished at the capacity of water to both save and destroy—Ishmael floats on a buoyant trunk after the Pequod is dismantled by the greatest creature of the sea—even as it binds all elements on earth together. Melville’s obsession with water is matched in Hawthorne by what Gaston Bachelard calls a “poetics of fire” (Smith 127). From Young Goodman Brown to Oberon, Dimmesdale, and Ethan Brand, characters in his fiction pass through baptisms of fire, and find themselves changed by its “creative-destructive or euphoric-ominous energy” (Bidney 58-9). Through fire in texts from “Main Street” to The House of the Seven Gables to Septimius Felton, Hawthorne finds the energy for an imaginative human life, for poetic genius and emotional purity, and for intimations of immortality, even as he engages this element as “Earth’s Holocaust” to burn whatever will not rise. These obsessive elemental engagements—whether the white-hot heat of Hawthorne or the watery melancholia of Melville—prove prophetic, not just as literary fulfillments of spiritual symbols, but as precursors to the apocalyptic end times of the Anthropocene, when life on earth is threatened by immersion in water and fire. Where Melville and Hawthorne can imagine and breathe life into the metaphysical possibilities of flooding and burning, those who read their work now must apprehend their oeuvre in the face of a world drowning in flames.